Label-free molecular profiling for identification of biomarkers in carcinogenesis using multimodal multiphoton imaging - Liu, Yuan; Tu, Haohua; You, Sixian; Chaney, Eric J.; Marjanovic, Marina; Boppart, Stephen A. (Quantitative Imaging in Medicine and Surgery; Vol 9, No 5 (May 31, 2019): Quantitative Imaging in Medicine and Surgery (Advanced Optical Imaging in Biomedicine Special Issue), 2019)
Background: Label-free molecular profiling, imaging, and analysis are of particular interest in cancer biology for detecting subtle biochemical changes during cancer progression and potentially during cancer treatment. Multimodal, multiphoton imaging that combines diverse molecular contrasts derived from different physical mechanisms can improve our understanding of the tumor microenvironment. Methods: A label-free optical molecular profiling technique has been developed based on penta-modal multiphoton imaging to investigate mammary tumor progression in a pre-clinical rat model. Pulses from a coherent supercontinuum were tailored for two-photon (2PF) and three-photon fluorescence (3PF), second (SHG) and third harmonic generation (THG), and hyperspectral coherent anti-Stokes Raman scattering (CARS)-based imaging. A graphic multiphoton molecular profiling model was constructed to intuitively combine the co-registered quantitative, chemical, functional, and structural tissue information, enabling longitudinal in situ biomolecular analysis. Results: Over a 9-week period of tumor progression, and even before the formation of solid tumor, we observed lipid-protein transitions, microenvironmental reorganization, and a shift from FAD to NAD(P)H fluorescence, which reflects the reprogramming of cellular metabolism in carcinogenesis. Conclusions: Multimodal multiphoton imaging reveals and interrelates diverse carcinogenic signatures, identifying biomarkers that could serve as early molecular indicators for breast cancer diagnosis. This quantitative multimodal imaging methodology for molecular profiling of associated cancer biomarkers may have a broader impact in fundamental cancer research and future clinical applications.